EFFECTIVENESS OF POVERTY REDUCTION POLICY IMPLEMENTATION IN PANGKEP DISTRICT - Mahrani, Rezky; Rukmana, Novayanti Sopia; Halim, Didin (Universitas Negeri Makassar, 2025)
This research aims to determine and describe the effectiveness of implementing poverty reduction policies in Pangkep Regency. This type of research is descriptive qualitative researchwith data collection techniques through observation, interviews and documentation. Meanwhile, checking the validity of the data is carried out through source triangulation. Data analysis techniques use data condensation, data presentation and conclusion drawing. The research results show that the effectiveness of implementing poverty reduction policies in Pangkep Regency hasnot been optimal. There are six dimensions that are taken into consideration when looking at the implementation of this policy, namely in terms of policy standards and targets, resources. characteristics of implementing agents, inter-organizational relationships, implementor dispositions and social, economic and political conditions. These six dimensions are obstacles in implementing and implementing poverty reduction policies in Pangkep Regency. that in general policy implementation is quite good, but it is hoped that the resource dimension can be improved and its availability maximized. Policy standards and targets so that the implementation of povertyreduction policies can run effectively and on target, as well as economic, social and political conditionsaround thelocation can be improved sothat theimplementation process ofthis Regional Regulation can run optimally. Dimensions of implementation disposition, characteristics of implementing agents and Inter-organizational relationships have been implemented optimally, this is due to strong will and good inter-organizational relationships in overcoming poverty in Pangkep Regency